Empowering Cilembu Sweet Potato Farmers Through Education and Utilization of Local Plant-Based Biopesticides: an Environmentally Friendly Solution to Reduce Dependence on Chemical Pesticides - Elly Roosma Ria; Kovertina Rakhmi Indriana; Ai Komariah; Rike Siti Latipah; Fahmi Shihabuddin (Pascasarjana Universitas Mataram, 2025)
Cilembu sweet potato farmers' dependence on synthetic chemical pesticides raises concerns about their impact on health, the environment, and agricultural sustainability. This Community Service Program (PKM) aims to empower farmers through education and training in the production of biopesticides from locally sourced plants. Implementation methods include outreach, demonstrations of biopesticide production from materials such as neem and soursop leaves, and hands-on field training. The results of the activities indicate an increase in farmers' understanding and skills in utilizing biopesticides as an environmentally friendly pest control alternative. The program concludes that education and utilization of locally sourced plant-based biopesticides have proven effective as a practical solution to reduce dependence on chemical pesticides while simultaneously supporting sustainable agriculture for Cilembu sweet potato farmers.